A case report on digoxin toxicity - Shereen, Shaima; Fareedullah, Mohammed; Jabeen, Raqshan (International Journal of Basic & Clinical Pharmacology, 2024)
Digoxin is an inotropic drug that is commonly prescribed in patient with heart related diseases. The effective dose of digoxin is 0.8-2.0 ng/ml beyond which digoxin causes toxic effects like visual dysfunction, irregular heartbeat, and cardiovascular collapse. Digoxin toxicity is caused due to increased automaticity and inotropy due to intracellular calcium and decreased dromotropy due to poisoning of sodium potassium transporter and AV nodal blockade. Digoxin toxicity should be assessed by continuous hemodynamic and cardiac monitoring including 12-lead electrocardiogram. There should be timely and immediate evaluation of electrolyte levels like potassium, calcium, serum creatinine and digoxin levels and prompt intensive care unit admission, if necessary. In this case study we studied a 43 old female patient prescribed with digoxin 0.25 mg, who had a medical history of congestive cardiac failure presented with symptoms of digoxin toxicity. The patient was assessed with electrocardiography (ECG) and managed by keeping digoxin on hold and effective patient counselling.